Modifikasi Makceting (Makanan Cegah Stunting) sebagai Bentuk Inovasi PMT di Desa Dorolegi Kecamatan Godong Kabupaten Grobogan - Wahyu Unggul Widodo; Deart Are Koeanda; Ahmad Yusuf Mufarihin; Eva Wulan Dari; Indah Fitriani; Alif Putra Dirgantara; Nurul Fahrian; Ayu Avitasari; Lutfia Atika Salma; Nova Ayyunda Sholehkhah (LPPM Akbid Harapan Ibu Pekalongan, 2026)
Stunting is a chronic nutritional problem that impacts physical growth, cognitive development, and the quality of human resources. The high prevalence of stunting in Grobogan Regency requires innovative and sustainable community-based interventions. One preventative measure is through the provision of supplementary feeding (PMT) based on local foods with high animal protein content. This activity aims to increase the knowledge and awareness of mothers of toddlers regarding the importance of animal protein intake through the PMT innovation